THE ROLE OF DROSOPHILA NUCLEAR RECEPTOR FTZ-F1 IN SOMATIC CELLS IS NECCESSARY FOR GERMLINE STEM CELL MAINTENANCE - Sanders, Sydney (East Carolina University, 2022)
The production of gametes is a controlled synergistic relationship between germ cells and somatic cells. In Drosophila oogenesis, the NR5A subfamily nuclear receptor ftz-f1 is expressed in the germline stem cells, germ cysts, somatic escort cells, and follicle cells. Ftz-f1 has been identified for its roles in oocyte production to promote egg chamber survival, germline stem cell maintenance, and ecdysteroid signaling. This paper identifies ftz-f1 in the escort cells as an important, but not a sole contributor, to germ cell encapsulation and oocyte specification. We also demonstrate that depletion of ftz-f1 in the escort cells and neurons results in a loss of germline stem cells from the niche that can be rescued by external supplement of ecdysone. Interestingly, we find that ftz-f1 is likely necessary in neural tissue only for germline stem cell maintenance. This study highlights the importance of somatic and germline cell communication and provides novel potential insight into long range signaling between the nervous system and reproductive systems.
Keywords: Germ cell; escort cell; Nuclear receptors (Biochemistry); Drosophila; Stem cells--Research